One of the Symbols of Colonialism Resistance in Lakssiba Region, Morocco. "Moha Ou Said Lwerrawi" as a Case Study - Amraoui, Mohammed; El Amrani, Mohamed (Jordan Journal for History and Archaeology, 2025)
This research presents the biography of Mouha Saïd El Weraoui (1856-1924) as a model of Moroccan tribal leaders who adapted to the major developments experienced by Moroccan society at the end of the 19th century and the beginning of the 20th century. Mouha Saïd emerged as a tribal leader who governed the Ait Wera tribe according to customs, but this phase did not last long; as the Makhzen armies soon reached his tribal territory, and he had to choose between obeying the Moroccan Sultan Hassan I or confronting his advancing armies toward the Middle Atlas Mountains in 1886. El Weraoui chose the first option and was appointed by the Moroccan Sultan as the leader of the Ait Isri federation. The third phase of Mouha Saïd’s life began in 1907 after the French colonial incursion into Casablanca, when he declared jihad, began mobilizing the tribes, and resisted colonization until his death in 1924. One of the main conclusions of this study is the role of the environment in which Mouha Saïd grew up in shaping his personality and forming his stances on the issues facing him.